2020
DOI: 10.1029/2019ja027656
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Complex Es Observed by Multi Instruments Over Low‐Latitude China

Abstract: A complex daytime sporadic E (Es) case with extremely high critical frequency (foEs) was observed over the low latitude of China on 19 May 2018. Simultaneous observational results from two very high frequency (VHF) radars, two ionosondes, and multiple Global Navigation Satellite System total electron content and scintillation receivers are analyzed to investigate the evolution of the complex Es occurrence, which consisted of a relatively weak ambient Es layer (foEs < 8 MHz) and band‐like strong Es structures (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Under such conditions, the MILs deform to patchy structures rather than planar ones on horizontal cross sections, Figures 6 and 11d-11f. Recent total electron content (TEC) researches have reported that horizontal shapes of the Es layer, the MIL appearing in the ionospheric E region, are characterized by narrow, elongated structures, which were typically elongated in the east-west direction both in the daytime and nighttime (e.g., Maeda & Heki, 2014Sun et al, 2020). In the TEC studies, TEC was detrended to detect Es layers.…”
Section: Discussionmentioning
confidence: 99%
“…Under such conditions, the MILs deform to patchy structures rather than planar ones on horizontal cross sections, Figures 6 and 11d-11f. Recent total electron content (TEC) researches have reported that horizontal shapes of the Es layer, the MIL appearing in the ionospheric E region, are characterized by narrow, elongated structures, which were typically elongated in the east-west direction both in the daytime and nighttime (e.g., Maeda & Heki, 2014Sun et al, 2020). In the TEC studies, TEC was detrended to detect Es layers.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that scintillations due to E s can be greatly influenced by the thickness of the layer, the elevation angle of ray paths, and the frequency of radio signals (e.g., Beach & Kintner, 1999;Kintner et al, 2007). Recent studies found that the scintillation level of GNSS signals also depends on the satellite constellation and the receiver type (e.g., Liu et al, 2019;Sun, Ning, et al, 2020). Whereas the correlation between ROTI and S 4 index was occasionally reported (e.g., Luo et al, 2018;Yang & Liu, 2016), a statistical correlation between strong E s irregularities and S 4 index based on ground-based GNSS observations is not performed yet.…”
Section: Correlation Between Hr-roti and Scintillationmentioning
confidence: 99%
“…The superimposed gray dots in the bottom panel represent the collocated S 4 index of BD-GEO satellites. This case was investigated bySun, Ning, et al (2020). The unique V-shape echoes were due to the process of strong E s structures/irregularities passing over the field of view of the ionosonde/VHF radar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the accuracy of STEC and spatial resolution in this analysis is not sufficient to resolve such density inhomogeneity. However, Sun et al (2020) have analyzed the high Doppler spectral width of the radar echoes in E s , which indicated severe perturbation inside the layer. The band-like main structure reach maximum in scale at ∼17:30 LT, which can be extended to ∼400 km in E-W. E s structures start to dissipate after around 17:42 LT, the lifetime of this strong E s with foEs exceeding 20 MHz can reach approximately 30 min.…”
Section: Event Of Doy 141 2010mentioning
confidence: 99%